2019
DOI: 10.3847/1538-4357/aaf9a9
|View full text |Cite
|
Sign up to set email alerts
|

Faraday Rotation in the Jet of M87 inside the Bondi Radius: Indication of Winds from Hot Accretion Flows Confining the Relativistic Jet

Abstract: We study Faraday rotation in the jet of M87 inside the Bondi radius using eight Very Long Baseline Array data sets, one at 8 GHz, four at 5 GHz, and three at 2 GHz. We obtain Faraday rotation measures (RMs) measured across the bandwidth of each data set. We find that the magnitude of RM systematically decreases with increasing distance from the black hole from 5,000 to 200,000 Schwarzschild radii. The data, showing predominantly negative RM sign without significant difference of the RMs on the northern and sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 206 publications
(318 reference statements)
12
101
0
Order By: Relevance
“…We are able to fit the the observed jet boundary shape with the theoretical curve in the parabolic domain with b ≈ 2.05 − 2.07, which is consistent with Bondi accretion flow models Quataert & Narayan (2000); Narayan & Fabian (2011). However, the direct measurements of a particle number density in ISM either by X-ray observations (Russell et al 2015), or by modelling the Faraday rotation measure on the ambient medium (Park et al 2019), provide n ∝ r −1 , which corresponds to smaller b for adiabatic flow. This caveat may be solved if the temperature rises closer to the central source, as was predicted by Quataert & Narayan (2000) and discussed in Russell et al (2015).…”
Section: Resultssupporting
confidence: 77%
“…We are able to fit the the observed jet boundary shape with the theoretical curve in the parabolic domain with b ≈ 2.05 − 2.07, which is consistent with Bondi accretion flow models Quataert & Narayan (2000); Narayan & Fabian (2011). However, the direct measurements of a particle number density in ISM either by X-ray observations (Russell et al 2015), or by modelling the Faraday rotation measure on the ambient medium (Park et al 2019), provide n ∝ r −1 , which corresponds to smaller b for adiabatic flow. This caveat may be solved if the temperature rises closer to the central source, as was predicted by Quataert & Narayan (2000) and discussed in Russell et al (2015).…”
Section: Resultssupporting
confidence: 77%
“…We note that our recent study of Faraday rotation in the jet at distances 2 × 10 5 R S suggests κ 2(Park et al 2019), which allows a parabolic jet shape without a transition to a conical shape(Komissarov et al 2009), as observed in this region.4 We note, however, that GRMHD simulations consistently found that gas outflows launched from the disk cannot reach relativistic speeds due to high mass-loading (e.g.,Sadowski et al 2013;Yuan et al 2015;Nakamura et al 2018;Qian et al 2018). …”
mentioning
confidence: 67%
“…Given that the jet position angle wobbles across the different observing epochs, we can argue that the RM variations are produced by variations of the path length (d l ) through the external Faraday screen and/or variations in the electron density distribution n e (Stirling et al 2003). The persistent negative sign in the observed RM across the different epochs, within the scenario in which the Faraday screen is mostly represented by the hot accretion flow or wind outflow, could be explained by a misalignment of the jet axis with respect to the wind axis (Park et al 2019). If compared to Mrk 421 (e.g.…”
Section: Polarisation Propertiesmentioning
confidence: 94%